Comparison of Video Prompting with and Without Voice‐Over Narration: A Replication with Young Children with Autism. (29th July 2016) - Gutierrez, Anibal; Bennett, Kyle D.; McDowell, Logan S.; Cramer, Elizabeth D.; Crocco, Christina
Abstract : We compared the effects of video prompting (VP) with and without voice‐over narration on the play skills of two young children with autism spectrum disorder using an adapted alternating treatment design. The results showed increases in play skills when using VP with and without voice‐over narration for both participants. These results suggest that the difference in effectiveness between VP with and without voice‐over narration may be negligible for some children with autism. Implications for the use of VP without additional teaching strategies and the need for additional component analyses are discussed. Copyright © 2016 John Wiley & Sons, Ltd.